Field performance of hand-mixed and machine-mixed asphalt in labour-based asphalt maintenance works. Issue Volume 18:Issued 3(2017) (4th March 2017) - Mhone, Limiton; Kikumoto, Mamoru
Abstract: Asphalt premix for labour-based maintenance works can be produced manually (hand-mixed) or by mechanised asphalt plants – the conventional method. Hand-mixed asphalt (HDMA), common especially in most developing countries, is claimed to equal machine-mixed asphalt (MMA) in terms of durability. Recently, however, there have been concerns about reduced durability of labour-based asphalt (LBA) works. The current study compared durability of HDMA and MMA with a view to establish suitable scope and appropriate traffic conditions for LBA maintenance works. The study was based on laboratory tests – on binder, aggregate and site premix – and field experiments which involved asphalt production and placement of small and big patches of HDMA and MMA on a heavily trafficked Likuni Road and a lightly trafficked Tsiranana Avenue in Lilongwe, Malawi. The study monitored the patch durability for two months after the maintenance work. Effects of the study variables – production method (HDMA and MMA), scope of works (small and big patches) and road category (heavily trafficked and lightly trafficked roads) – on patch durability were statistically analysed. The study has shown that production method affects durability of LBA the most. HDMA had 67% less durability than MMA. Scope of works and road class affected LBA durability by 27% and 23%, respectively. At a level of significance ( p -value) of 0.05, the effect of production method was significant, while that of patch size and work scope was not statistically significant. It is imperative of asphalt producers to adhere to proportions of premix components if quality of HDMA is to improve. Apart from improving the HDMA production process, the quality of LBA works could be improved by increasing contractors' access to MMA. The study recommends contractors' cooperation and adoption of production techniques (cost-cutting techniques) such as use of recycled asphalt pavement and warm mixture asphalts in order to improve contractors' access to MMA.